2018
DOI: 10.1021/acs.orglett.8b03368
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Intramolecular Double Hydroalkoxylation of Internal Alkynes

Abstract: Intramolecular double hydroalkoxylation of internal alkynes could be achieved using a Grubbs-type ruthenium carbene complex or its modified species to deliver a series of bridged-and spiroacetal derivatives in moderate to good yields. This study represents a new example of nonmetathetic reactions catalyzed by Grubbs-type ruthenium carbene complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 96 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…We have previously reported that the second-generation Hoveyda–Grubbs ( HG-II ) complex modified with DMF enables intramolecular double hydroalkoxylation of internal alkynes to provide a series of bridged- and spiroacetals in moderate to good yields (Scheme ). As an extension of our previous work, we envisioned that it might be similarly possible to synthesize spiroaminals under ruthenium catalysis. , Several groups have independently described gold-catalyzed alkyne double hydrofunctionalization for spiroaminal synthesis. , …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We have previously reported that the second-generation Hoveyda–Grubbs ( HG-II ) complex modified with DMF enables intramolecular double hydroalkoxylation of internal alkynes to provide a series of bridged- and spiroacetals in moderate to good yields (Scheme ). As an extension of our previous work, we envisioned that it might be similarly possible to synthesize spiroaminals under ruthenium catalysis. , Several groups have independently described gold-catalyzed alkyne double hydrofunctionalization for spiroaminal synthesis. , …”
Section: Resultsmentioning
confidence: 97%
“…Alkynes 1l–1o were prepared from homopropargylic alcohols 20a , b . Mesylation of 20a , b followed by azide displacement provided the corresponding azides, which were reduced with zinc (NH 4 Cl, THF/H 2 O, 50 °C) and then protected with TsCl/pyridine to deliver sulfonamides 21a , b .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On similar lines, Fuwa et al reported ruthenium-catalyzed double hydroalkoxylation of alkynyl diols 115 for the synthesis of bridge bicyclic dioxanes 116 in excellent yield (Scheme 46). [52] In these cases, aliphatic as well as aromatic alkynes gave good yields. However, an aromatic ring with electron-withdrawing groups indeed furnished a very less amount of product.…”
Section: Chemistry-a European Journalmentioning
confidence: 92%
“…Lately, a cycloisomerization approach by intramolecular dihydroalkoxylation of alkynyl diols catalysed by various transition metals such as Pd(II), Pt(II), Ir(I), Rh(I), Ru(II) and Au(I/III) has emerged as a more selective strategy. [11][12][13][14] This method offers specific advantages, as the alkyne acts as a masked carbonyl group, and the non-polar alkyne π-bonds being more compatible than ketones towards a number of common reaction conditions. 15 Gold catalysis has been a rapidly emerging field within transition metal catalysis in the past decade.…”
Section: Introductionmentioning
confidence: 99%